1979
DOI: 10.1001/archpedi.1979.02130100085017
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors in Diabetes Mellitus

Abstract: In this thorough review of the literature of the past 100 years concerning psychological factors in diabetes mellitus, interpretation is channeled toward adolescence. In addition, emphasis is given to the major role that emotional components play in the development and maintenance of the brittle teenage diabetic. The integration of adolescent developmental issues of into physician treatment plans is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Early research efforts repeatedly failed to identify a personality type which might predispose persons to diabetes (1,2). This initial failure may in part explain why personality measures were not routinely incorporated into clinical and research evaluations of patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Early research efforts repeatedly failed to identify a personality type which might predispose persons to diabetes (1,2). This initial failure may in part explain why personality measures were not routinely incorporated into clinical and research evaluations of patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…According to a controlled study (Greydanus and Hofmann 1979), diabetics, in particular those with poor control or long duration, are more depressive. Roger (1980) has reported recently that treatment with anti-depressant resulted in complete remission of PDN with concomitant relief of depression and return of depression test score.…”
Section: Results Of Psychological Testsmentioning
confidence: 99%
“…1994,24(4) study where the predisease period was 6 -10 years, Stein and Charles (1971) showed that 45% of diabetics had had an incidence of parental loss and family disturbance as compared to 16% of a control group. On the other hand, Kimball (1971) and Greydanus et al, (1979) argued that the relationship between the onset of diabetes and emotional stress has not yet been established. The subjects in the present study do not seem to have been subjected to undue stress before the onset of their illnesses although this was not specifically assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that such events are not mentioned could be seen as a shortcoming in the method used in this investigation in which unstructured questions elicit only that which the subject regards as important. On the other hand, the role played by stress in the onset of diabetes is by no means certain (Greydanus et al, 1979). There is a growing body of evidence which suggests that viruses or chemicals affect the immune system of people who may be genetically susceptible to diabetes (Craighead, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation